2016
DOI: 10.1108/qaoa-10-2015-0049
|View full text |Cite
|
Sign up to set email alerts
|

Learning from international experiences – developing older LGBT affirmative housing and care options in England

Abstract: Purpose – The purpose of this paper is to formulate recommendations from international and local examples to aid the design and delivery affirmative housing and care options for older LGBT individuals in England. Design/methodology/approach – This paper combines a desk-top review conducted by the author with personal views and recommendations for practice by discussing the levers within both the Care Act and Equality Act for greater LGBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…At the moment, older LGB&T people wanting to access specific older people's housing and care services are not able to choose an LGB&T service or indeed one that declares itself to be LGB&T affirmative (Ross, 2016). It is acutely apparent that one size will never fit all in provision for older LGB&T housing and that a range of alternatives should be available (Carr and Ross, 2013;Westwood, 2015Westwood, , 2016a.…”
Section: Solutionsmentioning
confidence: 99%
“…At the moment, older LGB&T people wanting to access specific older people's housing and care services are not able to choose an LGB&T service or indeed one that declares itself to be LGB&T affirmative (Ross, 2016). It is acutely apparent that one size will never fit all in provision for older LGB&T housing and that a range of alternatives should be available (Carr and Ross, 2013;Westwood, 2015Westwood, , 2016a.…”
Section: Solutionsmentioning
confidence: 99%
“…in one's existing home and whether they may experience prejudice or discrimination by those who they may encounter in their home, local area or if moving into some form of retirement or care home. Despite the concerns identified in these studies, the UK still has no LGBT*-specific later life housing provision, such as that found in other countries (Ross, 2016) and it is unclear exactly what form of housing older LGBT* people would prefer (King, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are two central issues: first, a lack of LGBT*-“friendly” or inclusive mainstream older age housing, care and support; second, a lack of specialist housing, care and support services dedicated to either older LGBT* people collectively, or to particular individuals/groups within the “LGBT*” umbrella. There are, at the time of writing, no such services in the UK, only a handful in Europe, by contrast with an ever-expanding number in the USA (Ross, 2016).…”
Section: Introduction To “Housing Care and Support For Older Lesbians Gay Bisexual And Trans* People”mentioning
confidence: 99%